Application of Role Playing Techniques to Increase Students’ Learning Motivation in the New Normal Period - Mahyuddin, Muhammad Junaedi; Sulaiman, Fitriyanti; Sudirman, M Yunus; Riska, Riska; Yanti, Yanti (Jurnal Basicedu, 2022)
The title of this study is "Application of Role Playing Techniques to Increase Students' Learning Motivation in Class V SDN 89 Uru in the New Normal Period." The pupils in this research were all in fifth grade at SDN 89 Uru. When provided to pupils, little learning motivation is shown, and just a few repetitions are appropriate to complete the job. The goal of this research was to see if using role-playing strategies may help pupils become more motivated to learn. A pre-experimental approach was used to perform this study. In this study, descriptive and inferential statistics were used to analyze the data. This is a class V research project involving 19 pupils. To make observations and distribute surveys, and subsequently draw conclusions, data gathering techniques were utilized. Learning motivation in class V SDN 89 Uru is in the high group, according to the research findings, with an average score of 84.65, a standard deviation of 7.03, and an ideal score of 200. The use of role playing tactics is now more common than it was previously.